Vulnerability and optimal probabilistic seismic demand model for curved and skewed RC bridges. (1st December 2018) - Serdar, Nina; Folić, Radomir
Highlights: Effects of bridge geometry and ground motion properties on seismic response are investigated. Probabilistic seismic (PS) demand models for skew and curved bridges are proposed. res PGV, res Sd (T1 ) and res Cord are found as most suitable measures to be used in PSA. Skewness increases bridge fragility, particularly for bridges with rectangular piers. Decrease of deck radius increases fragility, regardless the skewness and bent type. Abstract: The objective of this study is to investigate seismic response of bridges with unconventional configuration such as skewed and curved bridges. The influence of skewness and horizontal curvature on seismic performances of bridges, with a special focus on their influence on the probabilistic seismic demand model (PSDM), is analysed. Since the studies of seismic performances of bridges are nowadays formulated in probabilistic frameworks it is important that the established (PSDMs) meet specific criteria so they can be considered a reliable tool in seismic assessment of bridge structures. Twelve types of bridges are considered in this study by varying two bent types, three values of skewness and two values of curvature. Nonlinear dynamic analyses are conducted for all the considered samples. Longitudinal, transversal and resultant column drift ratios are considered as the bridge response. Five earthquake intensity measures are investigated and each of them are calculated from both horizontal components. In addition, the resultant measures are obtained by applying the SRSS rule on the components. The formed PSDMs are analysed in order to examine their efficiency, proficiency and sufficiency. Adverse effects of skewness and curvature on seismic performances of bridges are noticed in the conducted analyses by comparing mean values of column displacement ductility, established prediction models and fragility demand curves. It was noticed that these effects are more prominent for bridges with single pier bents with one weak direction in comparison with double pier bents. Finally, it is found that more accurate models (efficient and proficient) are obtained when structure dependant measures are used in PSDMs. Modified models including resultant measures and resultant response are proposed for fragility analysis of curved and skewed bridges.